Adaptive Learning Systems: Bridging Instructional Technology and Personalized Pedagogy through Design Thinking - Nwachukwu, Emmanuel Lucas; Egbue, Nwamaka Goodness; Victor-Nwakaku, Ijeoma (Darul Yasin Al Sys, 2025)
This review examines how adaptive learning systems, when guided by design thinking principles, can effectively bridge the disconnect between instructional technology and personalized pedagogy. While technological innovations continue to reshape educational environments, their transformative potential is often constrained by a lack of alignment with learner-centered instructional practices. The review contends that meaningful educational change requires more than the introduction of digital tools; it demands their deliberate integration through pedagogical strategies that respond to the needs of both learners and educators. Key instructional challenges addressed include large class sizes, learner heterogeneity, limited digital literacy, and insufficient feedback loops. Through the iterative stages of design thinking—empathizing, defining, ideating, prototyping, and testing—educators can systematically develop and refine solutions that address these complex issues. Within this framework, adaptive learning systems are positioned as critical enablers of personalized learning, offering differentiated pathways, real-time formative feedback, and data-driven instructional support. The review outlines a structured approach for integrating these systems into teaching practice, emphasizing the need to empower educators with actionable analytics, individualize learning trajectories, and cultivate inclusive classroom ecosystems. The findings underscore the pedagogical value of harmonizing design thinking with adaptive technologies to foster equity, responsiveness, and engagement in diverse educational settings. The review concludes that this integration transforms technology from a passive tool into an active pedagogical partner, with significant implications for educational innovation, teacher professional development, and policy frameworks aimed at advancing equitable, student-centered learning.